Exploring Phenotypes for Disease Resilience in Pigs Using Complete Blood Count Data From a Natural Disease Challenge Model - Bai, Xuechun; Putz, Austin M.; Wang, Zhiquan; Fortin, Frédéric; Harding, John C. S.; Dyck, Michael K.; Dekkers, Jack C. M.; Field, Catherine J.; Plastow, Graham S.; Canada, PigGen (Frontiers in Genetics, 2020)
Disease resilience is a valuable trait to help manage infectious diseases in livestock. It is anticipated that improved disease resilience will sustainably increase production efficiency, as resilient animals maintain their performance in the face of infection. The objective of this study was to identify phenotypes related to disease resilience using complete blood count (CBC) data from a wean-to-finish natural disease challenge model, established to mimic the disease pressure caused by many common pathogens at the commercial level of pig production. In total, 2433 crossbred Landrace and Yorkshire barrows that went through the natural disease challenge model were classified into four groups (resilient, average, susceptible, and dead) based on their divergent responses in terms of growth and individual treatment. Three sets of blood samples for CBC analysis were drawn at 2-weeks before, and at 2- and 6-weeks after the challenge: Blood 1, Blood 3, and Blood 4 respectively. CBC of Blood 1 taken from healthy pigs before challenge did not show differences between groups. However, resilient animals showed significantly higher increases in the concentration of lymphocytes from Blood 1 to Blood 3 at the early stage of infection, and for hemoglobin concentration and hematocrit from Blood 3 to Blood 4 at the late stage of infection (FDR < 0.05). The changes of neutrophil concentration from Blood 3 to Blood 4 in resilient and average animals were significantly lower than in susceptible and dead animals (FDR < 0.05). These results suggest that CBC traits could indicate a change in resource allocation between immunity and productivity following infection. Resilient animals are expected to show a faster initiation of adaptive immune responses and allocate more resources towards immunity during the infection stage. Therefore, resilient animals may recover earlier from infection, which could subsequently allow them to allocate more resources for maintaining high rates of production. The CBC traits in response to the challenge were found to be heritable and genetically correlated with growth and treatment, which may indicate the potential for developing CBC under disease or commercial conditions as a phenotype for genomic prediction of resilience by collecting data from commercial systems.